A stable new composite phase change material based on H2C2O4⋅2H2O-NH4Al(SO4)2⋅12H2O binary eutectic into ZrO2 modified expanded graphite. (March 2023) - Liao, Tingting; Luo, Fan; Liang, Xianghui; Wang, Shuangfeng; Gao, Xuenong; Zhang, Zhengguo; Fang, Yutang
Abstract: As energy shortage intensifies, improving energy efficiency and reducing energy consumption have become essential topics. Herein, a form-stable composite phase change material (FCPCM) consisting of modified expanded graphite (MEG) and eutectic hydrate was designed as a reliable and efficient thermal energy storage medium. Firstly, novel binary eutectic hydrate involving oxalic acid dihydrate (H2 C2 O4 .2H2 O) and ammonium aluminum sulfate dodecahydrate (NH4 Al(SO4 )2 .12H2 O) served as an excellent thermal energy storage guest. Zirconium dioxide (ZrO2 ) was used as a hydrophilic modifier because of its high heat resistance, high inertness, corrosion resistance, non-toxicity and countless hydrophilic groups. Therefore, the hydrophilic modified expanded graphite (MEG) as a supporting host was constructed by dip-coating of nano ZrO2 sol on the surface of expanded graphite (EG), which improved its hydrophilicity and compatibility with a eutectic guest. Compared with the original EG (83.05°), the contact angle of MEG containing 10 % ZrO2 on the water was decreased to 37.95°. In addition, the adsorption rate and capacity of MEG to binary eutectic were much faster and larger, reaching an approximate saturation (65.58 %) within 40 min, which was three times that of the untreated EG (23.10 %) in the same adsorption time. The resultant FCPCM containing 24 wt% MEG exhibited a good phase transition temperature (54.10 °C), high phase transition enthalpy (168.5 J/g), as well as excellent anti-leakage behavior. After 100 hot and cold cycles, the thermal performances of FCPCM kept relatively stable, which guaranteed its sustained thermal benefits. It provides a potential application in the field of solar phase change heat exchangers. Graphical abstract: Unlabelled Image Highlights: A novel binary eutectic hydrate phase change material is explored. Modified expanded graphite promotes high hydrophilicity and compatibility. A form-stable composite phase change material exhibits excellent thermal properties. The thermal performances of designed product have a satisfactory stability.